Women entrepreneurs' struggles during the COVID-19 pandemic and their use of social media - Ninik Sri Rahayu; Masduki; E. R. Nur Ellyanawati (Journal of Innovation and Entrepreneurship, 2023)
Small and medium enterprises (SMEs) throughout the world are facing a very complicated crisis due to COVID-19 pandemic and other structural challenges. This study is aimed at demonstrating the challenges faced by SMEs, particularly the struggles that women entrepreneurs of SMEs in Indonesia experienced to survive against these structural issues: COVID-19, digital presence and the male-dominated business sector in the country. Focusing on female-owned businesses in Yogyakarta, Indonesia, this paper carefully considers how social media platforms helped these businesses to continue. Using a descriptive quantitative approach, we collected data from 130 respondents and found that the COVID-19 pandemic has severely affected women entrepreneurs-especially those operating small and medium enterprises. They have experienced reduced income due to decreased sales, disrupted supply chains, difficulty paying credit instalments, and lack of access to government assistances. This study further sheds light on social media's important role in sustaining women-owned businesses. Facebook, WhatsApp, and Instagram have become the new tools through which women promote their products and reach new audiences. To overcome this issue, we advise a stronger government intervention to women-owned SMEs in the post-pandemic. Aside from managing social media for selling, we recommend women-owned small companies to internally intensify digital engagement, promotions, coupled by innovative products and attractive offers such as discounts.
Keywords: 650; COVID-19; Social media; SMEs; Struggles; Women entrepreneurs